WebCT in the classroom: taking the discussion to the Net - Hoggarth, Sean, author; De Miranda, Michael Anthony, author (Colorado State University. Libraries, 2006)
I want to create a poster that showed how I would use a webCT sort of program to hold discussion, peer-editing, and how that would lead to publishing of a student's work.
Keywords: discussion; peer-editing; publishing